HUBUNGAN ANTARA FREKUENSI KONSUMSI MAKANAN CEPAT SAJI DENGAN KEJADIAN OBESITAS PADA ANAK DI SD MUHAMMADIYAH 11 SURABAYA - Nurul Istiqomah, 131211133002 (2016)
Introduction: Obesity is a health problem that is increasing in the whole world. WHO (World Health Organization) states that obesity has become a global epidemic. Aim: The aim of the reasearch to explained related the frequency of fast food consumption of obesity in children with incident. Method: The research designed is analytic descriptive with cross sectional approach. Population of the research is student in Muhammadiyah 11 elementary school with 77 student as a samples. The independent variable that be measured frequency consumption fast food and dependent variable that be measured obesity in children. The research data accumulation by the instrument be in the form of questionnaire an analyzed with spearman rho statistik check. Result: The research outcomed evidence that frequency consumption fast food is significant result (P= 0,025), also have a significant result to obesity with incindent (P= 0,025). The next is better if expected to explain other factors associated related related the frequency of fast food consumption of obesity in children with incident in elementary school of Muhammadiyah 11 Surabaya